Correction: Application of a Sn4+ doped In2S3 thin film in a CIGS solar cell as a buffer layer. Issue 4 (29th January 2020) - Kim, SeongYeon; Mina, Md. Salahuddin; Kim, Kihwan; Gwak, Jihye; Kim, JunHo
Abstract : Correction for 'Application of a Sn 4+ doped In2 S3 thin film in a CIGS solar cell as a buffer layer' by SeongYeon Kim et al., Sustainable Energy Fuels, 2020, 4, 362–368.